1999
DOI: 10.1177/030089169908500617
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Chemoimmunotherapy in Metastatic Clear Cell Sarcoma: A Case Report

Abstract: Clear cell sarcoma is a rare tumor with a poor prognosis. The therapeutic approach in the metastatic disease stage is controversial: to the authors' knowledge the use of concurrent chemoimmunotherapy has not been previously reported. We present a case of a 57-year-old male with metastatic clear cell sarcoma treated simultaneously with subcutaneous interferon-a 2b and six courses of chemotherapy according to the CyVEDIC regimen. Disease stabilization lasting 17 months was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Steger et al [17] reported a 17-month complete response to perilesional interferon alpha 2b (administered for 4 months) in a 40-year-old woman with CCS, but there have been few other reports of the use of immunotherapy in this disease [18].…”
Section: Discussionmentioning
confidence: 99%
“…Steger et al [17] reported a 17-month complete response to perilesional interferon alpha 2b (administered for 4 months) in a 40-year-old woman with CCS, but there have been few other reports of the use of immunotherapy in this disease [18].…”
Section: Discussionmentioning
confidence: 99%
“…There is anecdotal evidence of clinical activity of interferon-alpha 2b in the setting of metastatic CCS. One patient achieved SD during 17 months after simultaneous treatment with subcutaneous interferon-alpha 2b and six courses of cyclophosphamide, vincristine, doxorubicin, and dacarbazine (CYVADIC) [46].…”
Section: Immunotherapymentioning
confidence: 99%
“…There have been case reports of responses to interferon in osteosarcoma [14, 15] and complete responses in clear cell sarcomas [16, 17]. From 1971 to 1990, 89 consecutive patients with localized high-grade osteosarcoma received adjuvant therapy with interferon- α .…”
Section: Nonspecific Immunomodulationmentioning
confidence: 99%